Difference between revisions of "009C Sample Midterm 2, Problem 3"

From Math Wiki
Jump to navigation Jump to search
(Replaced content with "<span class="exam">Determine convergence or divergence: <span class="exam">(a)  <math>\sum_{n=1}^\infty (-1)^n \sqrt{\frac{1}{n}}</math> <span class="exam">(b) &nbs...")
 
Line 5: Line 5:
 
<span class="exam">(b) &nbsp;<math>\sum_{n=1}^\infty (-2)^n \frac{n!}{n^n} </math>
 
<span class="exam">(b) &nbsp;<math>\sum_{n=1}^\infty (-2)^n \frac{n!}{n^n} </math>
  
 +
<hr>
 +
[[009C Sample Midterm 2, Problem 3 Solution|'''<u>Solution</u>''']]
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;
 
|-
 
|'''1.''' '''Alternating Series Test'''
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; Let &nbsp;<math>\{a_n\}</math>&nbsp; be a positive, decreasing sequence where &nbsp;<math style="vertical-align: -11px">\lim_{n\rightarrow \infty} a_n=0.</math>
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; Then, &nbsp;<math>\sum_{n=1}^\infty (-1)^na_n</math>&nbsp; and &nbsp;<math>\sum_{n=1}^\infty (-1)^{n+1}a_n</math>
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; converge.
 
|-
 
|'''2.''' '''Ratio Test'''
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; Let &nbsp;<math style="vertical-align: -7px">\sum a_n</math>&nbsp; be a series and &nbsp;<math>L=\lim_{n\rightarrow \infty}\bigg|\frac{a_{n+1}}{a_n}\bigg|.</math>
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; Then,
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; If &nbsp;<math style="vertical-align: -4px">L<1,</math>&nbsp; the series is absolutely convergent.
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; If &nbsp;<math style="vertical-align: -4px">L>1,</math>&nbsp; the series is divergent.
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; If &nbsp;<math style="vertical-align: -4px">L=1,</math>&nbsp; the test is inconclusive.
 
|-
 
|'''3.''' If a series absolutely converges, then it also converges.
 
|-
 
|
 
|}
 
  
 +
[[009C Sample Midterm 2, Problem 3 Detailed Solution|'''<u>Detailed Solution</u>''']]
  
'''Solution:'''
 
  
'''(a)'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|First, we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\sum_{n=1}^\infty (-1)^n \sqrt{\frac{1}{n}}=\sum_{n=1}^\infty (-1)^n \frac{1}{\sqrt{n}}.</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|We notice that the series is alternating.
 
|-
 
|Let &nbsp;<math> b_n=\frac{1}{\sqrt{n}}.</math>
 
|-
 
|First, we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math>\frac{1}{\sqrt{n}}\ge 0</math>
 
|-
 
|for all &nbsp;<math style="vertical-align: -3px">n\ge 1.</math>
 
|-
 
|The sequence &nbsp;<math>\{b_n\}</math>&nbsp; is decreasing since
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{1}{\sqrt{n+1}}<\frac{1}{\sqrt{n}}</math>
 
|-
 
|for all &nbsp;<math style="vertical-align: -3px">n\ge 1.</math>
 
|-
 
|Also,
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\lim_{n\rightarrow \infty}b_n=\lim_{n\rightarrow \infty}\frac{1}{\sqrt{n}}=0.</math>
 
|-
 
|Therefore, the series &nbsp;<math>\sum_{n=1}^\infty \frac{(-1)^n}{\sqrt{n}}</math>&nbsp; converges by the Alternating Series Test.
 
|}
 
 
'''(b)'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|We begin by using the Ratio Test.
 
|-
 
|We have
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\lim_{n\rightarrow \infty}\bigg|\frac{a_{n+1}}{a_n}\bigg|} & = & \displaystyle{\lim_{n\rightarrow \infty} \bigg| \frac{(-2)^{n+1} (n+1)!}{(n+1)^{n+1}} \frac{n^n}{(-2)^n n!}\bigg|}\\
 
&&\\
 
& = & \displaystyle{\lim_{n\rightarrow \infty} \bigg| (-2)(n+1) \frac{n^n}{(n+1)^{n+1}}\bigg|}\\
 
&&\\
 
& = & \displaystyle{\lim_{n\rightarrow \infty} 2\frac{n^n}{(n+1)^n}}\\
 
&&\\
 
& = & \displaystyle{2\lim_{n\rightarrow \infty} \bigg(\frac{n}{n+1}\bigg)^n.}
 
\end{array}</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Now, we need to calculate &nbsp;<math style="vertical-align: -15px">\lim_{n\rightarrow \infty} \bigg(\frac{n}{n+1}\bigg)^n.</math>
 
|-
 
|Let &nbsp;<math style="vertical-align: -15px">y=\lim_{n\rightarrow \infty} \bigg(\frac{n}{n+1}\bigg)^n.</math>
 
|-
 
|Then, taking the natural log of both sides, we get
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\ln y } & = & \displaystyle{\ln \bigg( \lim_{n\rightarrow \infty} \bigg(\frac{n}{n+1}\bigg)^n \bigg)}\\
 
&&\\
 
& = & \displaystyle{\lim_{n\rightarrow \infty} \ln \bigg(\frac{n}{n+1}\bigg)^n}\\
 
&&\\
 
& = & \displaystyle{\lim_{n\rightarrow \infty} n \ln \bigg(\frac{n}{n+1}\bigg) }\\
 
&&\\
 
& = & \displaystyle{\lim_{n\rightarrow \infty} \frac{\ln \bigg(\frac{n}{n+1}\bigg)}{\frac{1}{n}}}
 
\end{array}</math>
 
|-
 
|since we can interchange limits and continuous functions.
 
|-
 
|Now, this limit has the form &nbsp;<math style="vertical-align: -13px">\frac{0}{0}.</math>
 
|-
 
|Hence, we can use L'Hopital's Rule to calculate this limit.
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 3: &nbsp;
 
|-
 
|Now, we have
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\ln y } & = & \displaystyle{\lim_{n\rightarrow \infty} \frac{\ln \big(\frac{n}{n+1}\big)}{\frac{1}{n}}}\\
 
&&\\
 
& = & \displaystyle{\lim_{x\rightarrow \infty} \frac{\ln \big(\frac{x}{x+1}\big)}{\frac{1}{x}}}\\
 
&&\\
 
& \overset{L'H}{=} & \displaystyle{\lim_{x\rightarrow \infty} \frac{\frac{1}{\big(\frac{x}{x+1}\big)}\frac{1}{(x+1)^2}}{\big(-\frac{1}{x^2}\big)}}\\
 
&&\\
 
& = & \displaystyle{\lim_{x\rightarrow \infty} \frac{-x}{x+1}}\\
 
&&\\
 
& = & \displaystyle{-1.}
 
\end{array}</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 4: &nbsp;
 
|-
 
|Since &nbsp;<math>\ln y=-1,</math>&nbsp; we know
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>y=e^{-1}.</math>
 
|-
 
|Now, we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\lim_{n\rightarrow \infty} \bigg|\frac{a_{n+1}}{a_n}\bigg|=2e^{-1}=\frac{2}{e}.</math>
 
|-
 
|Since &nbsp;<math style="vertical-align: -13px">\frac{2}{e}<1,</math>&nbsp; the series is absolutely convergent by the Ratio Test.
 
|-
 
|Therefore, the series converges.
 
|}
 
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
|&nbsp; &nbsp; '''(a)''' &nbsp; &nbsp; converges (by the Alternating Series Test)
 
|-
 
|&nbsp; &nbsp; '''(b)''' &nbsp; &nbsp; converges (by the Ratio Test)
 
|}
 
 
[[009C_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]
 
[[009C_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 11:39, 12 November 2017

Determine convergence or divergence:

(a)  

(b)  


Solution


Detailed Solution


Return to Sample Exam